Pengaruh Tingkat Pendidikan terhadap Kepatuhan Penyampaian Su-rat Pemberitahuan Pajak Penghasilan (Studi Empiris pada Wajib Pajak di KPP Cikupa, Tigaraksa dan Tangerang Timur) - Antonius Juniarto (Departement of Mathematics Education, 2023)
Previous research stated that the level of education has a partial effect on taxpayer compliance. For this reason, it is necessary to analyze more deeply how the influence of education level on compliance with the submission of income tax notification letters (SPT). This study aims to examine whether there is a positive effect on the level of education of individuals on the delivery of income tax returns with empirical studies on taxpayers at the Cikupa Primary Tax Service Office, Tangerang. In addition to education level, gender and marital status of taxpayers are also associated. The research method used is causal, with the unit of analysis being individual taxpayers. The sampling method used Stratified random sampling. Level of education based on gender and status of individual taxpayers in submitting income tax returns is measured using a questionnaire instrument with a Likert scale. Data analysis was performed by descriptive analysis and linear regression. The results of this study are expected to provide contributions, references, information and empirical evidence needed for parties in need in relation to the level of education based on gender and the status of individual taxpayers for the submission of income tax returns.